2017
DOI: 10.1111/mcn.12542
|View full text |Cite
|
Sign up to set email alerts
|

Using cognitive mapping to understand Senegalese infant and young child feeding decisions

Abstract: Caregivers make decisions about how to feed their infants and young children based on complex interactions of knowledge, beliefs, and values, as well as assessments of situational determinants, including economic and social constraints and opportunities. Because of the relationship of these factors to the adoption of new feeding behaviours, the development of nutrition interventions for this age group must be grounded in knowledge about the target population. This paper presents the results of a study that use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…In many regions of Senegal, naturally fermented milk is known as lait caillé and forms an integral component of the daily diet. Recent ethnographic studies have documented the role of lait caillé in the complementary feeding diets of infants and young children in northern Senegal ( Zobrist et al, 2017 , 2018 ). The microbial community in milk drives the fermentation process and is of great importance for the shelf life, safety, nutritional, and organoleptic properties of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…In many regions of Senegal, naturally fermented milk is known as lait caillé and forms an integral component of the daily diet. Recent ethnographic studies have documented the role of lait caillé in the complementary feeding diets of infants and young children in northern Senegal ( Zobrist et al, 2017 , 2018 ). The microbial community in milk drives the fermentation process and is of great importance for the shelf life, safety, nutritional, and organoleptic properties of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently mentioned consideration of mothers to provide a snack to their young child was health. Likewise, previous studies identified health as an important food related value (Connors et al, 2001) and as driver of food choice by mothers (Walsh et al, 2015;Zobrist et al, 2018;Damen et al, 2019a). Child preference was another important motive for mothers to provide a snack.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, the study of Machín et al (2016) among low-income mothers of children aged 1-5 years revealed that mothers gave more importance to the healthiness of the food when selecting the foods for their children than for the adults living in their household. Johnson et al (2011), Walsh et al (2015), and Zobrist et al (2018) also identified health as an important diver for mothers' food choice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations